Providing a Structural Model of Early Helplessness in Cancer Patients based on Early Maladaptive Schemas (EMSs) and Coping Strategies with the Mediating Role of Family Codependency - Lotfihaqiqat, Amir; Monirpoor, Nader; ZarghamHajebi, Majid (Applied Family Therapy Journal (AFTJ), 2021)
Aim: This study was conducted to provide a structural model of family helplessness in cancer patients based on the early maladaptive schemas (EMSs) and coping strategies with the mediating role of family codependency. Methods: This was a descriptive study with a correlational design. The study population included all caregivers of cancer patients referred to the palliative care centers of Tehran's Firoozgar Hospital, the Cancer Research Center of Shahid Beheshti University of Medical Sciences, and the Cancer Research Center of the Ministry of Health and Medical Education in 2020, of which 300 people were selected as a sample using convenience sampling. The study tools were the Family Hardiness Index (FHI) (McCubbin, Thompson, and McCubbin, 1996), the Schema Questionnaire-Short Form (YSQ-SF) (Young, 1998), the Coping Inventory (Endler & Parker, 1980), and the Codependence Questionnaire (Stone Brink, 1998). The data were analyzed with Pearson's correlation coefficient, regression, and structural equation modeling (SEM) using SPSS and SmartPLS software. Results: According to the results, there is a significant positive relationship between EMSs and family helplessness (α ≤0.01), but not between coping strategies and family helplessness. The results also showed that there is a significant relationship between the EMSs and family codependency (α ≤0.01), family codependency and family helplessness, coping strategies and family codependency, and family codependency and family helplessness (α ≤0.01). Conclusion: As the EMSs increase, the family helplessness increases, and the family helplessness of the caregivers of cancer patients changes by 0.17 with a one-unit change in the EMSs according to the variable of family codependency. Besides, the family helplessness of caregivers of cancer patients changes by 0.18 units with a one-unit change in coping strategies according to the variable of family codependency.